Shear loading dominated damage mechanisms and strain localization studied by in situ 3D laminography imaging and Digital Volume Correlation for AA2198-T8. (March 2023) - Buljac, Ante; Kong, Xiang; Helfen, Lukas; Hild, François; Morgeneyer, Thilo F.
Abstract: Damage and strain changes during shear dominated loading were assessed in situ via synchrotron laminography. In combination with digital volume correlation (DVC), local strain fields inside the material were determined thanks to the contrast provided by intermetallic particles. Testing was performed on a thin sheet sample with an optimized geometry that induced shear stress states in two ligaments opposite to each other with respect to the loading axis. Examining one of the ligaments, the strain fields in the material showed the expected localization in the shear plane with a central peak in shear strain. The Lode parameter fields associated with incremental strain measurements were determined for the analyzed zone and found to be close to zero. The total Hencky von Mises strain close to failure was measured in the material bulk and reached values between 0.6 and 0.7 for a DVC element length of 20 μ m . In the shear zone, damage onset in the form of grain-related elongated cracks and of voids nucleating on intermetallic particles was detected from about half of the maximum value of the equivalent strain to failure onward. Voids between particle clusters grew in shear as the particles were rigid and mostly brittle. Damage was mainly concentrated in the gage section subjected to shear and away from free surfaces, in particular away from the notches. It was characterized and quantified with respect to the maximum equivalent strain found inside the band. Highlights: Damage development under simple shear was imaged by 3D in situ laminography 3D Strain fields were measured by DVC The Lode parameter was assessed based on strain increments Damage nucleated and grew in the aluminum alloy Shear and intermetallic particle cracks were found